Efeitos do extrato de Chlorella vulgaris e do EDTA sobre o tecido ósseo de ratos expostos ao acetato de chumbo - Ferreira, José Aparecido (Universidade Federal de São Carlos, 2013)
Lead acetate (Pb) is a nonessential and highly toxic heavy metal which is released to the environment by several routes, mainly by industrial and mining activities. Recent studies have suggested that lead caused a decrease in femur strength of adult rats. A wide range of chelating has been evaluated as possible protective agents against lead acetate toxicity. Dissodium ethylenediaminetetraacetate (Na2EDTA) is the chelating agent most widely used in the treatment of Pb poisoning. The chelating therapy with EDTA might induce Pb mobilization from inert deposition organs toward such critical tissues as the brain. But, it is questioned the safety of the use of this compound in the management of Pb poisoning. The lack of safety and efficacy demonstrated by conventional chelating has encouraged the search for new ways to remove heavy metals from the body. Recently, a supplementation of Chlorella vulgaris extract (CV) was shown to alleviate the heavy metals toxicity in rats. The aim of this study was to evaluate possible protective influence of Chlorella and Na2EDTA supplementation on bone physical and biomechanical properties of rats exposed to lead acetate. For this purpose, male Wistar rats were distributed into eight groups (n=8): Control (0.9% saline 0.1 ml/100g body weight- BW), EDTA (150 mg/Kg BW), CV 50 (50 mg/Kg BW), CV 250 (250 mg/Kg BW), Pb (250 mg/Kg BW), Pb (250 mg/Kg BW) plus EDTA (150 mg/Kg BW), Pb (250 mg/Kg BW) plus CV 50 (50 mg/Kg BW) and Pb (250 mg/Kg BW) plus CV 250 (250 mg/Kg BW). The treatment was done once a week, for 8 weeks by gastric gavage. Bone volume, bone mineral density (BMD) and biomechanical properties (maximum load, resilience and stiffness) of the femoral diaphysis and 5th lumbar vertebra were examined. The biomechanical properties of femurs were obtained by the three-points bending test and compression test for vertebrae, using a universal test machine Instron, model 4444. Bone MMP-2 activitie was measured by gelatin zymography. Concentrations of lead and zinc in whole blood and lead, zinc, calcium and magnesium in the left femur and 4th lumbar vertebra were determined by ICP-MS (Inductively Coupled Plasma Mass Spectrometry). Exposure to 250 mg/kg BW of Pb caused significant reduction of maximum load, stiffness and resilience indicating the ability of this element to damage the quality of bone tissue. In the 5th lumbar vertebrae, exposure to Pb caused significant reduction of bone mineral density. The treatment with Chlorella vulgaris (50 mg/kg BW and 250 mg/Kg BW) and EDTA (150 mg/Kg BW) during Pb exposure prevented the weakening of the bone strength. In the 5th lumbar vertebrae, the CV and EDTA prevented the reduction of bone mineral density due to Pb. The pro, intermediate and active MMP-2 activity in bone of animals exposed to lead showed a significant increase compared to control. The CV 50 administration in animals exposed to lead reduced the activity of MMP-2 isoforms in their pro, intermediate and active levels compared to control group. The exposure to Pb resulted in an increase of the blood concentration of this heavy metal and its accumulation in the liver, kidney, brain and bone concentration. The CV and EDTA reduced blood lead concentrations, leading to reduction of lead concentration in liver, kidney, brain and bone. These findings seem to indicate that treatment with Chlorella vulgaris and EDTA during exposure to Pb may be beneficial for the skeleton of subjects chronically exposed to Pb.
Keywords: Acetato de chumbo; Exposição crônica; Chlorella vulgaris; EDTA; Propriedades Biomecânicas Ósseas; MMP-2; Lead acetate; Chronic exposure, Chlorella vulgaris, EDTA, Bone biomechanical properties, MMP-2; CIENCIAS DA SAUDE